The precarity of internal migration of youth in Ghana: exploitative employment and livelihood insecurity. Issue 2 (17th February 2023) - Assan, Joseph Kweku; Kharisma, Dinar
ABSTRACT: This paper ascertains whether young internal migrants are prone to poverty and livelihood insecurity and become victims of exploitative employment when compared to the non-migrant youth population in Ghana. This study employs econometrics analysis using the Ghana Living Standards Survey 6 (2012) and 7 (2017), with a sample size of 15, 000 households, and ethnographic interviews to assess the determinants of livelihood security, exploitation, and abuse. Our analysis focuses on youth in four administrative regions in Ghana with the highest number of internal migrants. The study found that young internal migrants are often engaged in unstable, noncontract, abusive, and exploitative employment.